(untitled) (International Journal of Engineering and Computer Science, 2013)
In reliability analysis of a system using classical set theoretic approach or some statistical methods, we require exact knowledge about the functioning of the system. But in most of the cases, it is not possible to acquire the information to a high degree of exactness. This brings the importance of fuzzy set theory in reliability analysis. In this paper we shall study the failure mode screening methodology based upon fuzzy set theory.